The worst thing we've ever done: one juror's reckoning with racial injustice - Menaker, Carol (She Writes Press, 2023)
"In May of 1976, twenty-four-year-old Carol Menaker was impaneled with eleven others on a jury in the trial of Freddy Burton, a young Black prison inmate charged with the grisly murders of two white wardens inside Philadelphia's Holmesburg Prison. After being sequestered for twenty-one days, the jury voted to convict Mr. Burton, who was then sentenced to life in prison without parole. For more than forty years, Menaker did what she could to put the intensely emotional experience of the sequestration and trial behind her, rarely speaking of it to others and avoiding jury service when at all possible. But the arrival of a jury summons at her home in Northern California in 2017 set her on a path to unravel the painful experience of sequestration and finally ask the question: What ever happened to Freddy Burton--and is it possible that my youth and white privilege were what led me to convict him of murder? The Worst Thing We've Ever Done is Menaker's inspirational account of journeying back in time to uncover the personal bias that may have led her to judge someone whose shoes she never could have walked in." --